Computer models for the prediction of antimicrobial activity of 4-((5-(decylthio)-4-methyL-4H-1,2,4-triazol-3-yl)methyl)morpholine as a potential medicine - Ogloblina, M.; Bushuyeva, I. V.; Parchenko, V. V.; Gutiy, B.; Zazharskyi, V.; Davydenko, P.; Kulishenko, O.; Бушуєва, Інна Володимирівна; Парченко, Володимир Володимирович (My University, 2024)
The article is devoted to the polypharmacological profiling of 4-((5-(decylthio)-4-methyl- 4H-1,2,4-triazole-3-yl)methyl)morpholine, which has potential as an antimicrobial agent. The study was conducted using 15,148 electronic pharmacophore models of organisms, ranked according to the Tversky index. A detailed analysis of the compound’s interactions with selected enzymes showed that 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole-3- yl)methyl)morpholine forms classical types of bonds with chosen biotargets. The key amino acid residues involved in the formation of complexes were also identified. Based on the binding profiles observed for selected complexes with the active centers of thymidine kinase (4IVR), phosphate synthase (1G6C), and biotin carboxylase (2W6O), it can be concluded that this bioactive ligand is likely to exhibit antibacterial and antiviral effects by inhibiting molecular and biological processes in pathogenic organisms. The chosen targets had acceptable binding modes with 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole- 3-yl)methyl)morpholine, did not form unwanted contacts, and interacted with some critically important amino acid residues. This suggests the potential for further use in virtual screening, computer modeling, and more in-depth in vitro and in vivo studies. The results of the multitarget analysis could contribute to the development of new antimicrobial drugs effective against various types of infectious agents.
Keywords: 1,2,4-triazole; antifungal activity; biologically active compounds; computer models; molecular docking